PP242 Counteracts Glioblastoma Cell Proliferation, Migration, Invasiveness and Stemness Properties by Inhibiting mTORC2/AKT - Mecca, Carmen; Giambanco, Ileana; Bruscoli, Stefano; Bereshchenko, Oxana; Fioretti, Bernard; Riccardi, Carlo; Donato, Rosario; Arcuri, Cataldo (Frontiers in Cellular Neuroscience, 2018)
Glioblastoma multiforme (GBM) is the most malignant brain tumour and is associated with poor prognosis due to its thorny localization, lack of efficacious therapies, and complex biology. Among the numerous pathways driving GBM biology studied so far, PTEN/PI3K/AKT/mTOR signalling plays a pivotal role, as it controls cell survival, proliferation and metabolism and is involved in stem cell maintenance. In front of recent and numerous evidences highlighting mTOR upregulation in GMB, all the strategies developed to inhibit this pathway have been substantially unsuccessful. Our study focused on mTORC2 to understand its involvement in GBM cell growth, proliferation, migration, and invasiveness. We utilized an in vitro model, characterized by various genetic alterations (i.e. GL15, U257, U87MG, and U118MG cell lines) in order to achieve the clonal heterogeneity observed in vivo. Additionally, being the U87MG cell line endowed with glioblastoma stem cells (GSCs), we also investigated the role of the PTEN/PI3K/AKT/mTOR pathway in this specific cell population, which is responsible for GBM relapse. We provide further insights that explain the reasons for the failure of numerous clinical trials conducted to date targeting PI3K or mTORC1 with rapamycin and its analogues. Additionally, we show that mTORC2 might represent a potential clinically valuable target for GBM treatment, as proliferation, migration and GSC maintenance appear to be mTORC2-dependent. In this context, we demonstrate that the novel ATP-competitive mTOR inhibitor PP242 effectively targets both mTORC1 and mTORC2 activation and counteracts cell proliferation via the induction of high autophagy levels, besides reducing cell migration, invasiveness and stemness properties.